The Atlas Effect: Invisible workload can weigh down estheticians. - Talkovski, Marianne (Skin Deep)
The article focuses on the concept of the "invisible workload" faced by estheticians, which encompasses emotional labor, cognitive load, and administrative microtasks that are essential for client care and business success but often go unrecognized and unpaid. This hidden workload can lead to fatigue, burnout, and decreased financial success, as it detracts from the time and energy available for billable services. The article suggests strategies for estheticians to manage this workload effectively, such as scheduling time for administrative tasks, setting emotional boundaries, and redefining productivity metrics to enhance both personal well-being and business sustainability. Recognizing and addressing the invisible workload is presented as crucial for maintaining professional vitality and improving client satisfaction.